Comparison of microplastic isolation and extraction procedures from marine sediments. (October 2020) - Cashman, Michaela A.; Ho, Kay T.; Boving, Thomas B.; Russo, Stephen; Robinson, Sandra; Burgess, Robert M.
Abstract: Microplastics (MPs) are small (<5 mm) plastic particles which pose a threat to marine ecosystems. Identifying MPs is crucial for understanding their fate and effects. Many MP extraction methods exist, but procedural differences prevent meaningful comparisons across datasets. This method comparison examines the efficiency of five methods for extracting MPs (40–710 μm) from marine sediments. Known quantities of MPs were spiked into sediments. The MPs were extracted and enumerated to demonstrate percent recovery. Findings determined that sediment matrix, MP properties, and extraction method affect the percent recovery of MPs from sediments. Average recoveries of spiked microplastics were between 0 and 87.4% and varied greatly by sediment type, microplastic, and method of extraction. In general, larger particle and lower density MPs were more effectively recovered. Marine sediments low in organic matter and with larger grain size also had higher percent recoveries of MPs. These findings support the need for method optimization and unified procedures. Graphical abstract: Unlabelled Image Highlights: Microplastic and sediment physical properties affect extraction efficacy. Existing microplastic extraction methods preferentially extract microplastics based on physical properties. Smaller microplastics are more challenging to extract using conventional extraction methods. It is more difficult to extract microplastics from sediments high in organic matter.